The full-length transcript of the I factor, a LINE element of Drosophila melanogaster, is a potential bicistronic RNA messenger. - Bouhidel, K.; Terzian, C.; Pinon, H. (Nucleic Acids Research, 1994)
The I factor of Drosophila melanogaster is a retrotransposon of the LINE superfamily. The I factor displays two non-overlapping open reading frames (ORFs) that have the potential to encode for a nucleic acid-binding protein (ORF1) and a reverse transcriptase (ORF2). Retrotransposition of the I factor has been demonstrated and a putative full-length RNA intermediate has been identified. No other transcript from functional I factor has ever been described, suggesting that the full-length RNA is also used as a messenger. Here we report that a bicistronic RNA which conserves the ORF1-ORF2 organization of the I factor transcript is a template for ORF2 translation in vivo. We further demonstrate that the first AUG of ORF2 initiates translation, but efficiency of this initiation increases approximately 200 fold when ORF1 is deleted. Our results show that the I factor transcript may be used to translate both ORFs from their own initiation codons at different rates. Various mechanisms of translation are proposed.